2013
DOI: 10.1021/ic302511e
|View full text |Cite
|
Sign up to set email alerts
|

Argentivorous Molecules Bearing Two Aromatic Side-Arms: Ag+–π and CH−π Interactions in the Solid State and in Solution

Abstract: Seven double-armed cyclens bearing two aromatic side-arms, at the 1- and 7-positions of the cyclens, were prepared via three steps from dimethyl 2,2'-iminodiacetate. The X-ray structures of the Ag(+) complexes and Ag(+)-ion-induced (1)H NMR spectral changes suggest that the two aromatic side-arms cover the Ag(+) ions incorporated in the ligand cavities, as if the aromatic ring "petals" catch the Ag(+) ions in the way a real insectivorous plant (Venus flytrap) catches insects, using two leaves. It is also repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 78 publications
1
49
0
Order By: Relevance
“…The formation of the peak centered on 353 nm in the Zn II DB‐cyclen complex alone is of particular interest. One should stress that all attempts at model building based on structures of DB‐cyclen complexes like those reported here for the Pb II , Cu II , Ag I , or Cd II DB‐cyclen complexes, or for other similar complexes reported by Habata et al, indicate that formation of intramolecular exciplexes is rendered sterically impossible for N ‐benzyl groups placed on opposite nitrogen atoms of a cyclen type ligand. This is due to blocking of any such required π stacked structures required for the formation of an exciplex by ligands such as water or simple anions coordinated to the metal ion, and by the metal ion itself.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…The formation of the peak centered on 353 nm in the Zn II DB‐cyclen complex alone is of particular interest. One should stress that all attempts at model building based on structures of DB‐cyclen complexes like those reported here for the Pb II , Cu II , Ag I , or Cd II DB‐cyclen complexes, or for other similar complexes reported by Habata et al, indicate that formation of intramolecular exciplexes is rendered sterically impossible for N ‐benzyl groups placed on opposite nitrogen atoms of a cyclen type ligand. This is due to blocking of any such required π stacked structures required for the formation of an exciplex by ligands such as water or simple anions coordinated to the metal ion, and by the metal ion itself.…”
Section: Resultsmentioning
confidence: 53%
“…The Ag I has a square pyramidal geometry comprised of four Ag–N bonds averaging 2.477 ± 0.043 Å, plus two very short intermolecular η 2 Ag ··· C π contacts of 2.621 and 2.569 Å with an N ‐benzyl group from a neighboring Ag I DB‐cyclen complex. Habata et al have reported similar short intermolecular π contacts in [Ag(DB‐cyclen)]CF 3 SO 3 . Interestingly, they also report the Ag I structures of versions of DB‐cyclen with two bulkier aromatic substituents such as naphthyl and anthracenyl groups, and in these structures two intramolecular Ag ··· C π contacts are present.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Other substrates did not show this effect, thus suggesting that Ag-p interactions may be responsible for the increased ee value. [10,18] Gratifyingly,t he 1,1',2-trisubstituted alkenes (E)-8-12 gave good chemoselectivities and ee values for 8a-12 a ( Table 2, entries 8-12). The1 ,2,2'-substitution pattern in (E)-13 (entry 13) lowered the ee value to 22 %, although the yield and chemoselectivity remained high.…”
Section: Angewandte Chemiementioning
confidence: 96%